De(Re)Constructing Narratives in Intellectual Property Law: Transformative Play, Culture Jamming, and Poststructural Disruptions. Issue 1 (2nd January 2020) - Tan, David
Abstract: In his critique of consumption, Jean Baudrillard contends that the consumer no longer relates to a particular object in its specific utility, but to a set of objects in its total signification. Thus, increasingly, when consumers make their purchases, they do not simply select goods and services purely for their functional or utilitarian values, but are buying into the significations of these commodities in the construction of their self-identities. Objects of intellectual property (IP), in particular copyrighted works, trademarks and the celebrity personality, represent far more than a bundle of legal rights. They are invariably associated with a set of cultural narratives and semiotic meanings which are ultimately consumed. A well-known literary or artistic work does much more than simply educate, inform or entertain; it also functions as a signifier of a set of signified meanings. A trademark does not only designate the source or origin of goods. Famous brands like Louis Vuitton, Apple and Nike possess particular configurations of meanings that offer peculiarly powerful affirmations of belonging and recognition in the lives of their customers worldwide. Celebrities, whose identities may be protected against commercial appropriation by the right of publicity, have become common points of reference for millions of individuals who may never interact with one another, but who have, by virtue of their participation in a mediated culture, a shared experience and a collective memory. This essay explores how the encoded narratives in certain objects of IP may be read as polysemous texts that invite playful semiotic recodings, culture jamming and poststructural disruptions. It also suggests how audiences who engage with works of copyright, trademarks and celebrities via such textual signification may avail themselves of a number of legal defences under the current legal regime.